ASAS KONKORDANSI ISLAM DAN PANCASILA BAGI PERKEMBANGAN PERBANKAN SYARIAH DI INDONESIA - Darmalaksana, Wahyudin (IAIN Tulungagung, 2018)
This study analyzed the principles of concordance of Islamic law and Pancasila for the development of sharia banking in Indonesia. The growth of Islamic banking was overshadowed by the lack of Islamic economics sciences, so its development was experiencing infectivity in Indonesia. This study used the juridical-normative method of research subjects. In addition, the analysis was also conducted deductive and inductive to the legal materials. Basically, the essence of Islamic economics embodied in the principles of Islamic economics served as the foundation for the creation of Islamic economic sciences. However, the international Islamic world economic movement was more influential in the transformation of Islamic banking taqnin in Indonesia. In fact, the enforcement of the sharia banking legal system was constrained by the lopsided nature of the Islamic Banking Act with the potential of socio-economic support in the community. This study found that the principle of concordance between Islam and Pancasila in the development of sharia banking was seen to be possible from the philosophical aspect, but it was doubtful from the political aspect because of the impact of various economic systems in Indonesia. So, this study recommends the need for the formulation of Islamic banking system relevant to the socio-culture condition of Indonesian society.